Pilihan Forum Penyelesaian Sengketa Investasi - Ahmad Fajar Herlani (Nurani Hukum, 2020)
In investment activities between investors, the investment destination country (host country), the investment country of origin (home country) has different interests. In the course of investment activities, these interests often clash due to various factors in the recipient country. Conflicting interests will become a conflict for the parties and can harm materially and immaterial. The settlement of the conflict must be resolved with a win-win solution not to harm either party so that investors do not withdraw their capital from the recipient country. It is hoped that investment dispute resolution forums available in Indonesia or outside Indonesia can be used to resolve conflicts that occur with a win-win solution.Dalam kegiatan investasi antara investor, negara tujuan investasi (host country), negara asal investasi (home country)  mempunyai kepentingan yang berbeda. Dalam berjalannya kegiatan investasi seringkali kepentingan tersebut saling berbenturan karena berbagai faktor di Negara penerima. Kepentingan yang saling berbenturan akan menjadi konflik bagi para pihak dan bisa merugikan secara materil maupun immateril. Penyelesaian konflik tersebut harus diselesaikan dengan win-win solution tidak merugikan salah satu pihak sehingga investor tidak menarik modalnya dari Negara penerima. Diharapkan forum penyelesaian sengketa investasi yang tersedia di Indonesia ataupun diluar Indonesia dapat digunakan untuk menyelesaikan konflik yang terjadi dengan win-win solution.